2020
DOI: 10.5194/bg-17-727-2020
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of vegetation components and water level on methane dynamics in a boreal fen

Abstract: Abstract. Vegetation and hydrology are important controlling factors in peatland methane dynamics. This study aimed at investigating the role of vegetation components, sedges, dwarf shrubs, and Sphagnum mosses, in methane fluxes of a boreal fen under natural and experimental water level drawdown conditions. We measured the fluxes during growing seasons 2001–2004 using the static chamber technique in a field experiment where the role of the ecosystem components was assessed via plant removal treatments. The fir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 80 publications
0
24
0
1
Order By: Relevance
“…Instead, our findings are similar to patterns observed in other studies. WTD is a wellrecognized driver of CH 4 emissions Updegraff et al, 2001;Blodau et al, 2004;Turetsky et al, 2014;Riutta et al, 2020). Shallow WTD promote CH 4 emissions because methanogenesis requires anaerobic conditions, while deep WTD increases the portion of aerated surface peat accommodating consumption of CH 4 by methanotrophs as it diffuses toward the atmosphere Sundh et al, 1995).…”
Section: Methane Emissionsmentioning
confidence: 99%
“…Instead, our findings are similar to patterns observed in other studies. WTD is a wellrecognized driver of CH 4 emissions Updegraff et al, 2001;Blodau et al, 2004;Turetsky et al, 2014;Riutta et al, 2020). Shallow WTD promote CH 4 emissions because methanogenesis requires anaerobic conditions, while deep WTD increases the portion of aerated surface peat accommodating consumption of CH 4 by methanotrophs as it diffuses toward the atmosphere Sundh et al, 1995).…”
Section: Methane Emissionsmentioning
confidence: 99%
“…In addition to the direct effects of climate and hydrology on peatland C cycling and autogenic hydrological feedbacks that occur within peatlands (Waddington et al, 2015), changes in temperature and water table also indirectly influence C cycling through changes in the relative abundance and productivity of dominant plant functional types (PFTs; bryophyte, graminoid and ericoid) (Gavazov et al, 2018; Laine et al, 2011; Riutta, Korrensalo, Laine, Laine, & Tuittila, 2020). Warmer and drier conditions are predicted to favour a shift from bryophyte to vascular plant dominance (Buttler et al, 2015; Dieleman, Branfireun, McLaughlin, & Lindo, 2015; Walker, Ward, Ostle, & Bardgett, 2015), with implications for microclimates and GHG emissions (Gavazov et al, 2018; Radu & Duval, 2018; Robroek et al, 2015; Ward et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…the impact of the stream was again predominant over the impact of LAI. Studies have shown that shrubs can hinder CH4 production because of their poor-quality substrate for methanogenesis (Riutta et al, 2020, Yavitt et al, 2019, although the cover of shrubs at our study site was very small.…”
Section: Role Of Stream-induced Microhabitats In Driving Ch4 Emissionsmentioning
confidence: 66%
“…temperature or vegetation composition alone (Laine et al, 2019;Mäkiranta et al, 2018;Riutta et al, 2020). In addition to vertical water level changes, the lateral flow of water in fens can be even more important in driving the processes that underpin CH4 emissions, because flowing water not only ensures a water supply for the vegetation, but also transports nutrients, which benefits vegetation and microbial communities (Laitinen et al, 2007).…”
mentioning
confidence: 99%